A new delayed projection neural network for solving quadratic programming problems subject to linear constraints - Niu, Jiuxiao; Liu, Deyou (Applied mathematics and computation, 2012)
In this paper, a new projection neural network with two time delays is proposed for solving quadratic programming problems subject to linear constraints. And we give the existence of the continuous solution. By the theory of functional differential equation, the proposed neural network is proved to be globally exponentially stable under some conditions. Simulation results with some applications show the performance and characteristic of the proposed neural network.